Perbandingan Algoritma Levenshtein dan Jaro Winkler Pada Sistem Informasi Pencarian Dokumen Perundang-Undangan (Studi Kasus : Diskominfo Lahat) - Iqbal Syahputra; Firamon Syakti (LPPM UBHINUS MALANG, 2022)
This study can measure the comparison of the Levenshtein Distance calculation and Jaro Winkler's calculation in recognizing sentence similarity. The test information used in this review consists of two test information, namely test information to measure calculation closeness and test information to measure calculation handling time. The calculation test is completed by using a counterfeit identification application to calculate the level of comparability and handling time made by the two calculations. After testing, the data from the results of the two tests is calculated on average to calculate the comparison results. The result of the similarity comparison obtained from Jaro Winkler's calculation is 76%, while the Levensthein Distance calculation is 57%. Then the average result of Jaro Winkler's calculation is 0.0052 seconds, while the Levensthein Distance calculation is 0.00028 seconds. Based on the results of the comparison, Jaro Winkler's calculation proved to have a higher level of word similarity and a faster handling time than the calculation using Levenshtein Distance in identifying sentence similarity.